A high-flux nanofiltration membrane for nanofiltration concentration of lithium carbonate solution and preparation method thereof

The composite nanofiltration membrane was prepared by interfacial polymerization. The combination of boric acid-modified crown ether and polyamide porous base membrane was solved, and the existing nanofiltration membranes were effectively achieved in the Li+ selective separation and mechanical properties were achieved. Highly efficient Li+ adsorption and separation and improved membrane strength and flux were improved.

CN119656865BActive Publication Date: 2025-04-22安徽鑫纪源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510185375.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-22
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

The existing nanofiltration membranes are difficult to selectively separate Li+ in high magnesium lithium than salt lake brine, have low interception rate, insufficient structural strength and wear resistance, resulting in limited application in scenarios where high desalination is required.

Method used

High-throughput nanofiltration membrane was prepared by interfacial polymerization, and polyetherimide and functional modifiers such as boric acid-modified dibenzo-14-crown-4 were used to combine polyethyleneimine and 1,3,5-benzenetriacetic chloride to form a composite nanofiltration membrane with high selective adsorption ability and mechanical strength.

Benefits of technology

The selective adsorption and separation performance of the nanofiltration membrane to Li+ is significantly improved, the mechanical strength and permeability flux are enhanced, and the service life of the membrane is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-flux nanofiltration membrane for nanofiltration concentration of lithium carbonate solution and a preparation method thereof, which belongs to the technical field of nanofiltration membrane processing and is used to solve the problems of low permeation flux of nanofiltration membrane and Li + The invention relates to a technical problem of poor interception rate and weak impact resistance; the invention comprises the following steps: adding polyetherimide and dimethyl sulfoxide into a reactor and stirring, raising the temperature of the reactor to 60-70°C, stirring for 5-6 hours, obtaining a polyetherimide casting solution, coating a glass plate with the polyetherimide casting solution, and performing phase conversion to prepare a porous base membrane; the invention relates to a method for selectively adsorbing Li + The boric acid-containing crown ether, ethylenediamine and polyethyleneimine were prepared on the surface of polyamide-based membranes by interfacial polymerization. + The composite nanofiltration membrane with a channel can further improve the permeation flux of the nanofiltration membrane, Li + The retention rate capacity and structural strength extend its service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanofiltration membrane processing, and in particular to a high-flux nanofiltration membrane for nanofiltration concentration of lithium carbonate solution and a preparation method thereof. Background Art

[0002] Nanofiltration membrane is a membrane separation technology between ultrafiltration membrane and reverse osmosis membrane. Its unique pore size and charge effect make it stand out in the field of water treatment. It is mainly used to remove hardness (calcium and magnesium ions), organic matter, color and some salt in water. Compared with traditional water treatment methods such as coagulation and sedimentation, nanofiltration membrane is widely used in drinking water purification, industrial wastewater treatment, seawater desalination pretreatment, organic solvent treatment and other fields due to its high efficiency and energy saving. At the same time, nanofiltration membrane also shows great potential in the field of battery recycling such as lithium extraction from salt lake brine, separation of lithium carbonate solution, organic solvent treatment and other fields, becoming a multifunctional separation tool.

[0003] Although nanofiltration membranes have shown advantages in the separation of lithium-containing solutions, especially in the separation of magnesium and lithium in salt lake brine with a high magnesium-to-lithium ratio, as high-valent ions + The ratio increases, Li + The selective separation becomes more difficult. The nanofiltration membrane in the prior art has a low rejection rate for monovalent lithium ions, resulting in insufficient desalination effect. In addition, the membrane has a dense structure, and the recognition functional groups cannot be effectively exposed. The interior of the membrane is a dead-end channel, with large mass transfer resistance and low extraction efficiency. + Poor adsorption capacity and low retention rate limit its application in scenarios requiring high desalination;

[0004] Secondly, the structural strength of the nanofiltration membrane is poor. Under high pressure, the nanofiltration membrane is prone to structural collapse, deformation or rupture, which affects the stability and separation performance of the membrane. The nanofiltration membrane also has poor wear resistance. The surface of the nanofiltration membrane is easily damaged by friction from particulate impurities, resulting in decreased membrane performance or shortened life.

[0005] Therefore, nanofiltration membranes are very important in improving flux and selectively targeting the target element Li. + There are still certain technical challenges in terms of interception capacity and insufficient impact resistance. Summary of the invention

[0006] The purpose of the present invention is to provide a high-flux nanofiltration membrane for nanofiltration concentration of lithium carbonate solution and a preparation method thereof, which is used to solve the problems of nanofiltration membrane permeation flux, Li + There are technical issues that need to be further improved in terms of interception rate capacity and structural strength.

[0007] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of lithium carbonate solution, comprising the following steps:

[0008] S1, adding polyetherimide and dimethyl sulfoxide into a reaction kettle and stirring, raising the temperature of the reaction kettle to 60-70° C., stirring for 5-6 hours, obtaining a polyetherimide casting solution, coating a glass plate with the polyetherimide casting solution, and performing phase conversion to prepare a porous base membrane;

[0009] S2, adding a functional modifier and dimethyl sulfoxide into a reactor and stirring, raising the temperature of the reactor to 50-70°C, stirring for 8-10 hours, obtaining a functional modified liquid, coating the porous base membrane with the functional modified liquid, and coating and finishing to obtain a functional modified membrane, wherein the functional modifier is dibenzo-14-crown-4 modified with a boric acid group;

[0010] S3, adding ethylenediamine and polyethyleneimine solution into a reaction kettle and stirring, raising the temperature of the reaction kettle to 40-60°C, stirring for 5-6h to obtain a modified liquid, coating the modified liquid on the functional modified membrane, and coating and finishing to obtain a composite nanofiltration membrane precursor;

[0011] S4. Add 1,3,5-benzenetricarbonyl chloride and n-hexane solution into a reactor and stir. Under nitrogen protection, raise the temperature of the reactor to 40-60°C and stir for 5-6 hours to obtain an enhanced solution. Immerse the composite nanofiltration membrane precursor in the enhanced solution, take it out after immersion and penetration, and post-treat it to obtain a composite nanofiltration membrane.

[0012] Furthermore, in step S1, the amount ratio of polyetherimide and dimethyl sulfoxide is 20-30g:100-120mL, and the phase inversion finishing includes: after the reaction is completed, the polyetherimide casting liquid is placed in a dryer, allowed to stand for 24 hours, degassed, and blocked by a scraper 200-220 μm high from the casting glass slide, and then cast into deionized water at a temperature of 20-25°C, kept warm and soaked for 6 hours, taken out from the deionized water, washed with deionized water for 3-5 times, transferred to a drying oven at a temperature of 70-80°C, and dried to constant weight to obtain a porous base membrane.

[0013] Furthermore, in step S2, the dosage ratio of the functional modifier and dimethyl sulfoxide is 1-2g:10-12mL, and the coating finishing includes: coating the functional modification liquid on the porous base membrane, transferring it to an environment with a temperature of 40-60°C to react for 6-8h, soaking it in deionized water with a temperature of 50-60°C, soaking it for 2h, washing it with deionized water 3-5 times, transferring it to a drying oven with a temperature of 70-80°C, and drying it to constant weight to obtain a functional modified membrane.

[0014] Furthermore, the functional modifier is obtained by processing the following steps:

[0015] A1. Add catechol, lithium hydroxide, n-butanol and 1,3-dibromopropane into a reaction kettle and stir. Under nitrogen protection, raise the temperature of the reaction kettle to 100-110°C, keep the temperature for 6 hours, and perform post-treatment to obtain intermediate I.

[0016] The reaction equation for preparing intermediate I is:

[0017]

[0018] The reaction principle of intermediate I is:

[0019] During the reaction, catechol is activated by lithium hydroxide, which ionizes the hydroxyl molecules on the benzene ring. Under nitrogen protection, lithium hydroxide reacts with 1,3-dibromopropane to generate salts and oxygen ions. The oxygen ions react with the activated catechol to generate intermediate I by nuclear electron pair transfer.

[0020] The mass spectrometry analysis data of intermediate I are: 300.11 (100.0%), 301.11 (19.9%), 302.11 (2.6%).

[0021] A2, add intermediate I, chloroform, glacial acetic acid and nitric acid solution into a reaction kettle, stir, react at room temperature for 1 hour, raise the temperature of the reaction kettle to 50-60°C, keep the temperature for 6 hours, and post-treat to obtain intermediate II;

[0022] The reaction equation of intermediate II is:

[0023]

[0024] The reaction principle of intermediate II is:

[0025] Under the catalytic conditions of glacial acetic acid, the nitro group acts as an electrophilic reagent, and the nitro ion attacks the benzene ring to form a σ complex, which is then deprotonated to replace the hydrogen atom on the dibenzo-14-crown-4 benzene ring, and undergoes a secondary nitration reaction to generate intermediate II.

[0026] The mass spectrometry analysis data of intermediate II are: 390.08 (100.0%), 391.08 (20.0%), 392.08 (3.6%).

[0027] A3, intermediate II, anhydrous ethanol, palladium carbon, and hydrazine hydrate solution were added to a reaction kettle and stirred. Under nitrogen protection, the temperature of the reaction kettle was raised to 90-100°C, and the reaction was kept warm for 5 hours. After post-treatment, intermediate III was obtained;

[0028] The reaction equation of intermediate III is:

[0029]

[0030] The reaction principle of intermediate III is:

[0031] Under heating reaction conditions, hydrazine hydrate decomposes into hydrogen and nitrogen as reducing agents. The surface of the palladium-carbon catalyst adsorbs hydrogen to form active hydrogen atoms. The active hydrogen atoms are transferred from the palladium surface to the nitro group, reducing one of the nitrogen-oxygen double bonds to a single bond (N-OH) and forming a nitroso group. The generated nitroso group is reduced again by the active hydrogen atoms to form a hydroxylamine group. The hydroxylamine group is reduced again and loses water molecules to eventually form an amino group to generate intermediate III.

[0032] The mass spectrometry analysis data of intermediate III are: 330.13 (100.0%), 331.13 (19.9%), 332.13 (2.8%).

[0033] A4. Add intermediate III, methyl 4-carboxyphenylborate, N,N-dimethylformamide, triethylamine and molecular sieves into a reactor and stir. Under nitrogen protection, raise the temperature of the reactor to 40-60°C, react for 8-10 hours, and perform post-treatment to obtain a functional modifier.

[0034] The reaction equation of the functional modifier is:

[0035]

[0036] The reaction principle of the functional modifier is:

[0037] Under the alkaline catalyst conditions of triethylamine, the methoxy group on the boronic acid group of 4-carboxyphenylboronic acid methyl ester is replaced by the amino group on diaminodibenzo-14-crown-4 to form a boron-nitrogen bond. At the same time, the substituted methoxy group combines with another hydrogen atom of the amino group to release methanol, and the borate ester is connected to the molecular structure of the crown ether to generate a functional modifier.

[0038] The mass spectrometry analysis data of the functional modifiers are: 656.17 (100.0%), 655.17 (49.6%), 657.17 (36.1%), 656.18 (18.1%), 658.18 (6.8%), 654.18 (6.1%), 657.18 (4.3%), 658.17 (2.7%), 655.18 (2.2%), 659.18 (1.6%).

[0039] Furthermore, in step A1, the amount ratio of catechol, lithium hydroxide, n-butanol and 1,3-dibromopropane is 7-8g:6-7g:40-50mL:6-8mL, and the post-treatment includes: lowering the temperature of the reactor to 70-80°C, removing n-butanol by reduced pressure distillation, transferring the residue into a separatory funnel, adding dichloromethane and water for extraction, washing with water until neutral, taking the lower organic phase, evaporating to remove the dichloromethane solvent, washing the solid with anhydrous ethanol, and filtering to obtain intermediate I.

[0040] Furthermore, in step A2, the ratio of the intermediate I, chloroform, glacial acetic acid and nitric acid mixture is 5-6 g: 130-140 mL: 90-100 mL: 30-40 mL, and the post-treatment includes: raising the temperature of the reactor to 70-80° C., removing chloroform by reduced pressure distillation, washing with anhydrous ethanol, filtering, placing the filter cake in a vacuum drying oven at 70° C., and drying to constant weight to obtain intermediate II.

[0041] Furthermore, in step A3, the ratio of the intermediate II, anhydrous ethanol, palladium carbon, and hydrazine hydrate mixed solution is 5-6g:60-70mL:1g:80-90mL, and the post-treatment includes: cooling to room temperature, filtering to remove palladium carbon, transferring the filtrate to a reactor with a water bath temperature of 70-80°C, and removing the organic solvent by reduced pressure distillation to obtain intermediate III.

[0042] Furthermore, in step A4, the intermediate III, methyl 4-carboxyphenylborate, N,N-dimethylformamide, triethylamine, and molecular sieve are used in a ratio of 1-2 g: 2-3 g: 20-30 mL: 20-30 mL: 1 g, and the post-treatment includes: after the reaction is completed, raising the temperature of the reactor to 70-80° C., and removing the organic solvent by reduced pressure distillation to obtain a functional modifier.

[0043] Furthermore, in step A4, the preparation method of 4-carboxyphenylboronic acid methyl ester is: 4-carboxyphenylboric acid, methanol, p-toluenesulfonic acid, molecular sieves, and toluene are added to a reactor and stirred. Under nitrogen protection, the temperature of the reactor is increased to 50-60° C., and the reaction is kept warm for 6 hours, and 4-carboxyphenylboronic acid methyl ester is obtained by post-treatment.

[0044] Furthermore, the 4-carboxyphenylboric acid, methanol, p-toluenesulfonic acid, molecular sieve, and toluene are used in a ratio of 10-20 g: 30-40 mL: 4-6 g: 4-6 g: 1000-1100 mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 70-80° C., washing with sodium bicarbonate to neutrality, removing the organic solvent by reduced pressure distillation, washing with anhydrous ethanol, filtering, placing the filter cake in a 70° C. vacuum drying oven, and drying to constant weight to obtain 4-carboxyphenylboric acid methyl ester.

[0045] The reaction equation of 4-carboxyphenylboronic acid methyl ester is:

[0046]

[0047] The synthetic reaction mechanism of methyl 4-carboxyphenylborate is:

[0048] With p-toluenesulfonic acid as an acid catalyst, the hydroxyl group in 4-carboxyphenylboronic acid reacts with methanol to undergo an esterification reaction, removing water molecules to generate 4-carboxyphenylboronic acid methyl ester.

[0049] Mass spectrometry analysis data are: 180.06 (100.0%), 179.06 (24.8%), 181.06 (8.8%), 180.07(2.2%).

[0050] Further, in step S3, the amount ratio of ethylenediamine and polyethyleneimine solution is 2-4g:100-200mL, and the polyethyleneimine and methanol solution are used in a ratio of 2g:100mL to prepare the polyethyleneimine solution, and the coating finishing includes: coating the modified liquid on the functional modified membrane, transferring it to an environment with a temperature of 40-60°C for crosslinking for 5h, soaking it in deionized water at a temperature of 50-60°C, soaking it for 2h, washing it with deionized water for 3-5 times, and obtaining a composite nanofiltration membrane precursor, step In step S4, the dosage ratio of 1,3,5-benzene trimesoyl chloride and n-hexane solution is 0.1-0.2g:100-150mL, and the post-treatment includes: transferring the composite nanofiltration membrane precursor with the enhancing liquid to a nitrogen-protected tubular furnace at a temperature of 40-60°C, keeping it warm for 6 hours, soaking it in anhydrous ethanol at a temperature of 50-60°C, keeping it warm for 2 hours, using anhydrous ethanol 3-5 times, placing it in a drying oven at a temperature of 65-75°C and drying it to constant weight to obtain a composite nanofiltration membrane.

[0051] The synthetic reaction mechanism of the composite nanofiltration membrane is:

[0052]

[0053]

[0054] Where: , “*” indicates the active linking site of the organic chain segment.

[0055] The synthetic reaction mechanism of the composite nanofiltration membrane is:

[0056] Amine monomers (ethylenediamine, polyethyleneimine, crown ether) in the aqueous phase diffuse to the liquid-liquid interface, and 1,3,5-trimethylbenzenecarboxylic acid chloride in the organic phase also diffuses to the liquid-liquid interface. A thin polymer film is formed at the interface through interfacial polymerization reaction. This film will gradually grow into the organic phase or aqueous phase. The crown ether monomer directly combines with polyethyleneimine by hydrogen bonds, and the acyl chloride group of 1,3,5-trimethylbenzenecarboxylic acid chloride reacts with the amino group of amines to form an amide bond and release hydrogen chloride.

[0057] The invention also provides a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution, which is prepared by a method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution.

[0058] The present invention has the following beneficial effects:

[0059] 1. The aminodibenzo-14-crown-4 of the present invention can form a stable complex with Li⁺ ions by virtue of its macrocyclic structure through spatial matching and proton bridge bond exchange mechanism. Furthermore, through the esterification reaction with methyl 4-carboxyphenylboronic acid, the boric acid group with strong lithium affinity is introduced into the crown ether, which significantly improves the affinity to Li + The affinity of Li+ enhances the selective adsorption capacity. At the same time, the amino or amide groups on the polyamide porous base membrane also participate in the adsorption process by forming hydrogen bonds or coordination bonds with Li+. + Forming multiple points of bonding, this not only improves Li + The adsorption capacity of the composite nanofiltration membrane was improved, and the adsorption rate was accelerated, so that the composite nanofiltration membrane finally prepared was + It exhibits excellent performance in selective adsorption and separation.

[0060] 2. The present invention uses an interfacial polymerization method to directly polymerize the acyl chloride monomer on the polyetherimide base film, so that the 1,3,5-trimethylbenzenecarboxylic acid chloride monomer directly reacts with the amino group on the base film cross-linked by ethylenediamine and polyethyleneimine. In addition, the amino group carried by the aminodibenzo-14-crown-4 molecule itself also participates in the reaction, further increasing the cross-linking density and the metal ion coordination site. 1,3,5-trimethylbenzenecarboxylic acid chloride, as a trifunctional acyl chloride monomer, can undergo amidation reaction with the amino groups in ethylenediamine and polyetherimide to form a cross-linked polyamide layer. Ethylenediamine has a linear molecular structure and mainly forms linear segments during the cross-linking process, which contribute to the mechanical strength and toughness of the membrane. Polyetherimide, as a branched polyamine, has multiple amino groups on its side chain that can undergo multiple cross-linking with 1,3,5-trimethylbenzenecarboxylic acid chloride to construct a denser network structure, thereby improving the permeation flux of the membrane.

[0061] 3. The design of the composite nanofiltration membrane of the present invention cleverly integrates multiple mechanisms of action, showing a significant synergistic effect. The precise recognition ability of the crown ether and the lithium affinity of the boric acid group first pre-identify and complex Li in the solution. + , reducing the competition with other hydrated ions. Then, the polyamide-based membrane serves as a supporting structure, and the amino / amide groups on its surface further capture and fix the crown ether-complexed Li + , effectively avoiding Li + The dissociation and loss in the membrane pores were tested by the dynamic cycle adsorption method to test the separation performance of lithium ions relative to magnesium ions. The test showed that the composite porous nanofiltration membrane prepared by the phase inversion method had good performance on Li + The selective adsorption and separation show excellent performance. In addition, the interfacial polymerization design of this polyamine system can also regulate the micromorphology of the polyamide layer. The reaction of linear ethylenediamine and trifunctional acyl chloride tends to form a relatively flat polyamide structure, while branched polyethyleneimine will introduce more dendrites and defects during the cross-linking process, thereby improving the material transfer rate and permeation flux. At the same time, the dense network formed by multiple cross-linking realizes the separation of molecules of different sizes. The synergistic effect of this multiple action mechanism and microstructure regulation enables the composite nanofiltration membrane to not only maintain high Li + Selective adsorption and separation efficiency can also improve the permeability as well as the mechanical strength and toughness of the nanofiltration membrane. DETAILED DESCRIPTION

[0062] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0063] Example 1

[0064] This embodiment provides a method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution, comprising the following steps:

[0065] S1. Preparation of porous base membrane

[0066] Weigh: 200 g of polyetherimide and 1000 mL of dimethyl sulfoxide are added to a reactor and stirred. The temperature of the reactor is raised to 60° C. and stirred for 5 hours to obtain a polyetherimide casting solution. The polyetherimide casting solution is coated on a glass plate. After the reaction is completed, the polyetherimide casting solution is placed in a dryer and allowed to stand for 24 hours for degassing. After being blocked by a scraper with a height of 220 μm from the casting glass slide, the casting solution is cast into deionized water at a temperature of 20° C., and the casting solution is kept warm and soaked for 6 hours. The casting solution is removed from the deionized water, washed with deionized water 5 times, and transferred to a drying oven at a temperature of 70° C. and dried to a constant weight to obtain a porous base film.

[0067] S2. Preparation of functional modified membrane

[0068] Weigh: 700 g of catechol, 600 g of lithium hydroxide, 4000 mL of n-butanol, and 600 mL of 1,3-dibromopropane, add into a reactor and stir, under nitrogen protection, raise the temperature of the reactor to 100° C., reflux for 6 h, lower the temperature of the reactor to 70° C., remove n-butanol by vacuum distillation, transfer the residue into a separatory funnel, add dichloromethane and water for extraction, wash with water until neutral, take the lower organic phase, evaporate to remove the dichloromethane solvent, wash the solid with anhydrous ethanol, and filter to obtain intermediate I;

[0069] Weigh: 500 g of intermediate I, 13000 mL of chloroform, 9000 mL of glacial acetic acid, and 3000 mL of nitric acid solution, add into a reactor and stir, react at room temperature for 1 h, raise the temperature of the reactor to 50°C, reflux for 6 h, raise the temperature of the reactor to 70°C, remove chloroform by vacuum distillation, wash with anhydrous ethanol, filter, place the filter cake in a 70°C vacuum drying oven, and dry to constant weight to obtain intermediate II;

[0070] Weigh: 500 g of intermediate II, 6000 mL of anhydrous ethanol, 100 g of palladium carbon, and 8000 mL of hydrazine hydrate solution into a reactor and stir. Under nitrogen protection, the temperature of the reactor is raised to 90° C., refluxed for 5 h, cooled to room temperature, and the palladium carbon is removed by suction filtration. The filtrate is transferred to a reactor with a water bath temperature of 70° C., and the organic solvent is removed by reduced pressure distillation to obtain intermediate III;

[0071] Weigh: 100 g of 4-carboxyphenylboric acid, 300 mL of methanol, 40 g of p-toluenesulfonic acid, 40 g of molecular sieves, and 10,000 mL of toluene, add into a reactor and stir, under nitrogen protection, raise the temperature of the reactor to 50°C, reflux for 6 hours, after the reaction is completed, raise the temperature of the reactor to 70°C, wash with sodium bicarbonate to neutrality, remove the organic solvent by reduced pressure distillation, wash with anhydrous ethanol, filter, place the filter cake in a 70°C vacuum drying oven, and dry to constant weight to obtain 4-carboxyphenylboronic acid methyl ester;

[0072] Weigh: 100 g of intermediate III, 200 g of methyl 4-carboxyphenylborate, 2000 mL of N,N-dimethylformamide, 2000 mL of triethylamine, and 100 g of molecular sieves, add them into a reactor and stir, under nitrogen protection, raise the temperature of the reactor to 40° C., react for 8 h, after the reaction is completed, raise the temperature of the reactor to 70° C., remove the organic solvent by reduced pressure distillation, and obtain a functional modifier;

[0073] Weigh: 100 g of functional modifier and 1000 mL of dimethyl sulfoxide, add into a reactor and stir, raise the temperature of the reactor to 50°C, stir for 8 hours, obtain a functional modified liquid, coat the functional modified liquid on the porous base membrane, transfer it to an environment with a temperature of 40°C to react for 6 hours, soak it in deionized water at a temperature of 50°C, soak it for 2 hours, wash it with deionized water 5 times, transfer it to a drying oven at a temperature of 70°C, dry it to constant weight, and obtain a functional modified membrane.

[0074] S3, Composite nanofiltration membrane precursor

[0075] Weigh: 200 g of ethylenediamine and 10,000 mL of polyethyleneimine solution, add them into a reactor and stir, raise the temperature of the reactor to 40°C, stir for 5 hours, obtain a modified liquid, coat the modified liquid on the functional modified membrane, transfer it to an environment with a temperature of 40°C for cross-linking for 5 hours, soak it in deionized water at a temperature of 50°C for 2 hours, and wash it with deionized water 5 times to obtain a composite nanofiltration membrane precursor.

[0076] S4, composite nanofiltration membrane

[0077] Weigh: 10 g of 1,3,5-benzenetricarbonyl chloride and 10000 mL of n-hexane solution, add them into the reactor and stir. Under nitrogen protection, the temperature of the reactor is raised to 40°C and stirred for 5 hours to obtain an enhancement solution. The composite nanofiltration membrane precursor is immersed in the enhancement solution and taken out after soaking and penetration. The composite nanofiltration membrane precursor with the enhancement solution is transferred to a nitrogen-protected tubular furnace at a temperature of 40°C and kept warm for 6 hours. It is immersed in anhydrous ethanol at a temperature of 50°C and soaked for 2 hours. It is washed with anhydrous ethanol 5 times and placed in a drying oven at a temperature of 65°C and dried to constant weight to obtain a composite nanofiltration membrane.

[0078] Example 2

[0079] This embodiment provides a method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution, comprising the following steps:

[0080] S1. Preparation of porous base membrane

[0081] Weigh: 250 g of polyetherimide and 1100 mL of dimethyl sulfoxide are added to a reactor and stirred. The temperature of the reactor is raised to 65°C and stirred for 5.5 hours to obtain a polyetherimide casting liquid. The polyetherimide casting liquid is coated on a glass plate. After the reaction is completed, the polyetherimide casting liquid is placed in a dryer and allowed to stand for 24 hours for degassing. After being blocked by a scraper at a height of 200 μm from the casting glass slide, it is cast into deionized water at a temperature of 23°C, kept warm and soaked for 6 hours, taken out of the deionized water, washed 5 times with deionized water, transferred to a drying oven at a temperature of 75°C, and dried to constant weight to obtain a porous base membrane.

[0082] S2. Preparation of functional modified membrane

[0083] Weigh: 750 g of catechol, 650 g of lithium hydroxide, 4500 mL of n-butanol, and 700 mL of 1,3-dibromopropane, add them into a reactor and stir. Under nitrogen protection, the temperature of the reactor is raised to 105° C. and refluxed for 6 hours. The temperature of the reactor is lowered to 75° C., and n-butanol is removed by distillation under reduced pressure. The residue is transferred into a separatory funnel, and dichloromethane and water are added for extraction. The residue is washed with water until neutral. The lower organic phase is taken and evaporated to remove the dichloromethane solvent. The solid matter is washed with anhydrous ethanol and filtered to obtain intermediate I.

[0084] Weigh: 550 g of intermediate I, 13500 mL of chloroform, 9500 mL of glacial acetic acid, and 3500 mL of nitric acid solution, add into a reactor and stir, react at room temperature for 1 h, raise the temperature of the reactor to 55°C, reflux for 6 h, raise the temperature of the reactor to 75°C, remove chloroform by vacuum distillation, wash with anhydrous ethanol, filter, place the filter cake in a vacuum drying oven at 70°C, and dry to constant weight to obtain intermediate II;

[0085] Weigh: 550 g of intermediate II, 6500 mL of anhydrous ethanol, 100 g of palladium carbon, and 8500 mL of hydrazine hydrate solution into a reactor and stir. Under nitrogen protection, the temperature of the reactor is raised to 95° C., refluxed for 5 h, cooled to room temperature, and the palladium carbon is removed by suction filtration. The filtrate is transferred to a reactor with a water bath temperature of 75° C., and the organic solvent is removed by reduced pressure distillation to obtain intermediate III;

[0086] Weigh: 150 g of 4-carboxyphenylboric acid, 350 mL of methanol, 50 g of p-toluenesulfonic acid, 50 g of molecular sieves, and 10500 mL of toluene, add into a reactor and stir. Under nitrogen protection, the temperature of the reactor is raised to 55°C and refluxed for 6 hours. After the reaction is completed, the temperature of the reactor is raised to 75°C, washed with sodium bicarbonate until neutral, and the organic solvent is removed by reduced pressure distillation. The mixture is washed with anhydrous ethanol and filtered. The filter cake is placed in a vacuum drying oven at 70°C and dried to constant weight to obtain 4-carboxyphenylboric acid methyl ester.

[0087] Weigh: 150 g of intermediate III, 250 g of methyl 4-carboxyphenylborate, 2500 mL of N,N-dimethylformamide, 2500 mL of triethylamine, and 100 g of molecular sieves, add them into a reactor and stir, under nitrogen protection, raise the temperature of the reactor to 50° C., react for 9 hours, after the reaction is completed, raise the temperature of the reactor to 75° C., remove the organic solvent by reduced pressure distillation, and obtain a functional modifier;

[0088] Weigh: 150 g of functional modifier and 1100 mL of dimethyl sulfoxide, add into a reactor and stir, raise the temperature of the reactor to 60°C, stir for 9 hours, obtain a functional modified liquid, coat the functional modified liquid on the porous base membrane, transfer it to an environment with a temperature of 50°C to react for 7 hours, soak it in deionized water at a temperature of 55°C, soak it for 2 hours, wash it with deionized water 5 times, transfer it to a drying oven at a temperature of 75°C, dry it to constant weight, and obtain a functional modified membrane.

[0089] S3, Composite nanofiltration membrane precursor

[0090] Weigh: 300 g of ethylenediamine and 15000 mL of polyethyleneimine solution, add into a reactor and stir, raise the temperature of the reactor to 50°C, stir for 5.5 hours, obtain a modified liquid, coat the modified liquid on the functional modified membrane, transfer it to an environment with a temperature of 50°C for cross-linking for 5 hours, soak it in deionized water at a temperature of 55°C for 2 hours, and wash it with deionized water 5 times to obtain a composite nanofiltration membrane precursor.

[0091] S4, composite nanofiltration membrane

[0092] Weigh: 15 g of 1,3,5-benzenetricarbonyl chloride and 14000 mL of n-hexane solution, add them into the reactor and stir. Under nitrogen protection, the temperature of the reactor is raised to 50°C and stirred for 5.5 hours to obtain an enhancement solution. The composite nanofiltration membrane precursor is immersed in the enhancement solution and taken out after soaking and penetration. The composite nanofiltration membrane precursor with the enhancement solution is transferred to a nitrogen-protected tubular furnace at a temperature of 50°C and kept warm for 6 hours. It is then immersed in anhydrous ethanol at a temperature of 55°C and soaked for 2 hours. It is washed with anhydrous ethanol 5 times and placed in a drying oven at a temperature of 70°C and dried to constant weight to obtain a composite nanofiltration membrane.

[0093] Example 3

[0094] This embodiment provides a method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution, comprising the following steps:

[0095] S1. Preparation of porous base membrane

[0096] Weigh: 300 g of polyetherimide and 1200 mL of dimethyl sulfoxide are added to a reactor and stirred. The temperature of the reactor is raised to 70°C and stirred for 6 hours to obtain a polyetherimide casting liquid. The polyetherimide casting liquid is coated on a glass plate. After the reaction is completed, the polyetherimide casting liquid is placed in a dryer and allowed to stand for 24 hours for degassing. After being blocked by a scraper at a height of 220 μm from the casting glass slide, it is cast into deionized water at a temperature of 25°C, kept warm and soaked for 6 hours, taken out of the deionized water, washed 5 times with deionized water, transferred to a drying oven at a temperature of 80°C, and dried to constant weight to obtain a porous base membrane.

[0097] S2. Preparation of functional modified membrane

[0098] Weigh: 800 g of catechol, 700 g of lithium hydroxide, 5000 mL of n-butanol, and 800 mL of 1,3-dibromopropane, add them into a reactor and stir. Under nitrogen protection, the temperature of the reactor is raised to 110° C. and refluxed for 6 h. The temperature of the reactor is lowered to 80° C., and n-butanol is removed by distillation under reduced pressure. The residue is transferred into a separatory funnel, and dichloromethane and water are added for extraction. The residue is washed with water until neutral. The lower organic phase is taken and evaporated to remove the dichloromethane solvent. The solid matter is washed with anhydrous ethanol and filtered to obtain intermediate I.

[0099] Weigh: 600 g of intermediate I, 14000 mL of chloroform, 10000 mL of glacial acetic acid, and 4000 mL of nitric acid solution, add into a reactor and stir, react at room temperature for 1 h, raise the temperature of the reactor to 60°C, reflux for 6 h, raise the temperature of the reactor to 80°C, remove chloroform by vacuum distillation, wash with anhydrous ethanol, filter, place the filter cake in a vacuum drying oven at 70°C, and dry to constant weight to obtain intermediate II;

[0100] Weigh: 600 g of intermediate II, 7000 mL of anhydrous ethanol, 100 g of palladium carbon, and 9000 mL of hydrazine hydrate solution into a reactor and stir. Under nitrogen protection, the temperature of the reactor is raised to 100° C., refluxed for 5 h, cooled to room temperature, and the palladium carbon is removed by suction filtration. The filtrate is transferred to a reactor with a water bath temperature of 80° C., and the organic solvent is removed by reduced pressure distillation to obtain intermediate III;

[0101] Weigh: 200 g of 4-carboxyphenylboric acid, 400 mL of methanol, 60 g of p-toluenesulfonic acid, 60 g of molecular sieves, and 11000 mL of toluene, add into a reactor and stir. Under nitrogen protection, the temperature of the reactor is raised to 60°C, and refluxed for 6 hours. After the reaction is completed, the temperature of the reactor is raised to 80°C, and the reactor is washed with sodium bicarbonate until neutral. The organic solvent is removed by reduced pressure distillation, and the reactor is washed with anhydrous ethanol. The filter cake is placed in a vacuum drying oven at 70°C and dried to constant weight to obtain methyl 4-carboxyphenylborate;

[0102] Weigh: 200 g of intermediate III, 300 g of methyl 4-carboxyphenylborate, 3000 mL of N,N-dimethylformamide, 3000 mL of triethylamine, and 100 g of molecular sieves, add them into a reactor and stir, under nitrogen protection, raise the temperature of the reactor to 60° C., react for 10 h, after the reaction is completed, raise the temperature of the reactor to 80° C., remove the organic solvent by reduced pressure distillation, and obtain a functional modifier;

[0103] Weigh: 200 g of functional modifier and 1200 mL of dimethyl sulfoxide, add into a reactor and stir, raise the temperature of the reactor to 70°C, stir for 10 hours, obtain a functional modified liquid, coat the functional modified liquid on the porous base membrane, transfer it to an environment with a temperature of 60°C to react for 8 hours, soak it in deionized water at a temperature of 60°C, soak it for 2 hours, wash it with deionized water 5 times, transfer it to a drying oven at a temperature of 80°C, dry it to constant weight, and obtain a functional modified membrane.

[0104] S3, Composite nanofiltration membrane precursor

[0105] Weigh: 400 g of ethylenediamine and 20,000 mL of polyethyleneimine solution, add them into a reactor and stir, raise the temperature of the reactor to 60°C, stir for 6 hours, and obtain a modified liquid. Coat the modified liquid on the functional modified membrane, transfer it to an environment with a temperature of 60°C for cross-linking for 5 hours, soak it in deionized water at a temperature of 60°C for 2 hours, and wash it with deionized water 5 times to obtain a composite nanofiltration membrane precursor.

[0106] S4, composite nanofiltration membrane

[0107] Weigh: 20 g of 1,3,5-benzenetricarbonyl chloride and 15000 mL of n-hexane solution are added to a reactor and stirred. Under nitrogen protection, the temperature of the reactor is raised to 60°C and stirred for 6 hours to obtain an enhancement solution. The composite nanofiltration membrane precursor is immersed in the enhancement solution and taken out after soaking and penetration. The composite nanofiltration membrane precursor with the enhancement solution is transferred to a nitrogen-protected tubular furnace at a temperature of 60°C and kept warm for 6 hours. It is then immersed in anhydrous ethanol at a temperature of 60°C and soaked for 2 hours. It is washed with anhydrous ethanol 5 times and placed in a drying oven at a temperature of 75°C and dried to constant weight to obtain a composite nanofiltration membrane.

[0108] Comparative Example 1

[0109] The difference between this comparative example and Example 3 is that in step S2, methyl 4-carboxyphenylborate is not added.

[0110] Comparative Example 2

[0111] The difference between this comparative example and Example 3 is that in step S3, no modifying liquid is added.

[0112] Comparative Example 3

[0113] The difference between this comparative example and Example 3 is that in step S4, no enhancing liquid is added.

[0114] Performance Test:

[0115] The performance of the high-flux nanofiltration membrane for nanofiltration concentration of the lithium carbonate solution prepared in Examples 1-3 and Comparative Examples 1-3 was tested, wherein the pure water flux of the sample was determined according to the standard GB / T 34242-2017 "Nanofiltration Membrane Detection Method", and the tensile properties of the sample were determined according to the standard HY / T 213-2016 "Determination Method for Breaking Tensile Strength of Hollow Fiber Ultra / Microfiltration Membrane".

[0116] The retention rate of samples for Li2CO3 salt solutions of different concentrations was tested using a cross-flow membrane performance evaluation device. + The interception rate calculation formula is: × 100%, where C p and C f The conductivity of the salt solution on the permeate side and the feed side, respectively, in μS·cm -1 .

[0117] Lithium-magnesium separation performance determination:

[0118] Configuration containing Li + and Mg 2+ A mixed aqueous solution of two ions, with a concentration of 50 mg / L -1 Then fix the sample in the membrane pool and take 100mL of the sample with a concentration of 50mgL -1 Li + and Mg 2+ The mixed solution of the two ions was subjected to dynamic cyclic adsorption for 5 h at 25 °C. The concentrations of different ions before and after adsorption were measured by ICP-AES. + Relative to Mg 2+ The selectivity of the ion separation factor ( ), the calculation formula is: , where C Li is the Li in the permeate + Ion concentration, unit: g·L -1 ; C Mg is the Mg in the permeate 2+ Ion concentration, unit: g·L -1 ; C Li is the Li in the feed solution + Ion concentration, unit: g·L -1 ; C Mg is the Mg in the feed solution 2+ Ion concentration, unit: g·L -1 ; When the separation factor When the nanofiltration membrane is2+ Ions and Li + The separation of ions has no effect; when When 2+ Ions and Li + The separation of ions is effective, and The larger the value, the better the separation performance. The specific test results are shown in Table 1.

[0119] Table 1-Performance test data of the sample

[0120]

[0121] Data Analysis:

[0122] It can be seen from the relevant data in Table 1 that compared with the comparative example, the high-throughput nanofiltration membrane for nanofiltration concentration of lithium carbonate solution provided by the present invention introduces a Li selectively adsorbable nanoparticle on the surface of the polyamide-based membrane by interfacial polymerization. + The nanofiltration membrane obtained by using crown ether containing boric acid group, ethylenediamine and branched polyethyleneimine can significantly improve the flux of nanofiltration membrane, Li + The retention rate, breaking strength and breaking elongation can be improved, thereby extending its service life.

[0123] Comparative Example 1 is compared with Examples 1-3. + Retention rate, Li + / Mg 2+ The separation coefficient decreased, indicating that the modified crown ether, through the esterification reaction with methyl 4-carboxyphenylboronic acid, introduced the boric acid group with strong lithium affinity into the crown ether, which significantly improved the affinity to Li + The affinity of nanofiltration membranes is enhanced, and the selective adsorption capacity is enhanced. This composite structure significantly improves the nanofiltration membrane's + adsorption separation ability.

[0124] Compared with Examples 1-3, the breaking strength and breaking elongation of Comparative Example 2 are reduced, indicating that ethylenediamine has a linear molecular structure and mainly forms linear segments during the cross-linking process, which contribute to the mechanical strength and toughness of the membrane, thereby improving the mechanical properties of the nanofiltration membrane.

[0125] Compared with Examples 1-3, the pure water flux of Comparative Example 3 decreased significantly, indicating that polyetherimide, as a branched polyamine, can undergo multiple cross-linking with 1,3,5-trimethylbenzenecarboxylic acid chloride on its side chain to construct a denser network structure, thereby improving the permeation flux of the membrane.

[0126] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of lithium carbonate solution, characterized in that: The following steps are involved: S1, adding polyetherimide and dimethyl sulfoxide into a reaction kettle and stirring, raising the temperature of the reaction kettle to 60-70° C., stirring for 5-6 hours, obtaining a polyetherimide casting solution, coating a glass plate with the polyetherimide casting solution, and performing phase conversion to prepare a porous base membrane; S2, adding a functional modifier and dimethyl sulfoxide into a reactor and stirring, raising the temperature of the reactor to 50-70°C, stirring for 8-10 hours, obtaining a functional modified liquid, coating the porous base membrane with the functional modified liquid, and coating and finishing to obtain a functional modified membrane, wherein the functional modifier is dibenzo-14-crown-4 modified with a boric acid group; S3, adding ethylenediamine and polyethyleneimine solution into a reaction kettle and stirring, raising the temperature of the reaction kettle to 40-60°C, stirring for 5-6h to obtain a modified liquid, coating the modified liquid on the functional modified membrane, and coating and finishing to obtain a composite nanofiltration membrane precursor; S4. Add 1,3,5-benzenetricarbonyl chloride and n-hexane solution into a reactor and stir. Under nitrogen protection, raise the temperature of the reactor to 40-60°C and stir for 5-6 hours to obtain an enhanced solution. Immerse the composite nanofiltration membrane precursor in the enhanced solution, take it out after immersion and penetration, and post-treat it to obtain a composite nanofiltration membrane.

2. The method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution according to claim 1, characterized in that: In step S1, the polyetherimide and dimethyl sulfoxide are used in a ratio of 20-30g:100-120mL, and the phase inversion finishing includes: after the reaction is completed, the polyetherimide casting liquid is placed in a dryer, left to stand for 24 hours, degassed, and blocked by a scraper 200-220 μm high from the casting glass slide, and then cast into deionized water at a temperature of 20-25°C, soaked in water for 6 hours, removed from the deionized water, washed with deionized water for 3-5 times, transferred to a drying oven at a temperature of 70-80°C, and dried to constant weight to obtain a porous base membrane.

3. The method for preparing a high-throughput nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution according to claim 1, characterized in that: In step S2, the dosage ratio of the functional modifier and dimethyl sulfoxide is 1-2g:10-12mL, and the coating finishing includes: coating the functional modification liquid on the porous base membrane, transferring it to an environment with a temperature of 40-60°C to react for 6-8h, soaking it in deionized water with a temperature of 50-60°C, soaking it for 2h, washing it with deionized water 3-5 times, transferring it to a drying oven with a temperature of 70-80°C, and drying it to constant weight to obtain a functional modified membrane.

4. The method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution according to claim 1, characterized in that: The functional modifier is obtained by processing the following steps: A1. Add catechol, lithium hydroxide, n-butanol and 1,3-dibromopropane into a reaction kettle and stir. Under nitrogen protection, raise the temperature of the reaction kettle to 100-110°C, keep the temperature for 6 hours, and perform post-treatment to obtain intermediate I. A2, add intermediate I, chloroform, glacial acetic acid and nitric acid solution into a reaction kettle, stir, react at room temperature for 1 hour, raise the temperature of the reaction kettle to 50-60°C, keep the temperature for 6 hours, and post-treat to obtain intermediate II; A3, intermediate II, anhydrous ethanol, palladium carbon, and hydrazine hydrate solution were added to a reaction kettle and stirred. Under nitrogen protection, the temperature of the reaction kettle was raised to 90-100°C, and the reaction was kept warm for 5 hours. After post-treatment, intermediate III was obtained; A4. Add intermediate III, methyl 4-carboxyphenylborate, N,N-dimethylformamide, triethylamine and molecular sieves into a reactor and stir. Under nitrogen protection, raise the temperature of the reactor to 40-60°C, react for 8-10 hours, and perform post-treatment to obtain a functional modifier.

5. The method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution according to claim 4, characterized in that: In step A1, the amount ratio of catechol, lithium hydroxide, n-butanol and 1,3-dibromopropane is 7-8g:6-7g:40-50mL:6-8mL; in step A2, the amount ratio of intermediate I, chloroform, glacial acetic acid and nitric acid mixed solution is 5-6g:130-140mL:90-100mL:30-40mL; in step A3, the amount ratio of intermediate II, anhydrous ethanol, palladium carbon and hydrazine hydrate mixed solution is 5-6g:60-70mL:1g:80-90mL; in step A4, the amount ratio of intermediate III, methyl 4-carboxyphenylborate, N,N-dimethylformamide, triethylamine and molecular sieve is 1-2g:2-3g:20-30mL:20-30mL:1g.

6. The method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution according to claim 4, characterized in that: In step A4, the preparation method of 4-carboxyphenylboronic acid methyl ester is as follows: 4-carboxyphenylboric acid, methanol, p-toluenesulfonic acid, molecular sieves, and toluene are added into a reaction kettle with stirring; under nitrogen protection, the temperature of the reaction kettle is raised to 50-60° C., the reaction is kept warm for 6 hours, and 4-carboxyphenylboronic acid methyl ester is obtained by post-treatment.

7. The method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution according to claim 6, characterized in that: The 4-carboxyphenylboric acid, methanol, p-toluenesulfonic acid, molecular sieve and toluene are used in a ratio of 10-20 g: 30-40 mL: 4-6 g: 4-6 g: 1000-1100 mL.

8. The method for preparing a high-flux nanofiltration membrane for nanofiltration concentration of a lithium carbonate solution according to claim 1, characterized in that: In step S3, the dosage ratio of ethylenediamine and polyethyleneimine solution is 2-4g:2-4g:100-200mL, and the polyethyleneimine and methanol solution are used in a dosage ratio of 2g:100mL to prepare the polyethyleneimine solution. The coating finishing includes: coating the modified liquid on the functional modified membrane, transferring it to an environment with a temperature of 40-60°C for crosslinking for 5h, soaking it in deionized water with a temperature of 50-60°C for 2h, and washing it with deionized water for 3-5 times to obtain a composite nanofiltration membrane precursor. In step S4, the dosage ratio of 1,3,5-benzene trimesoyl chloride and n-hexane solution is 0.1-0.2g:100-150mL.

9. A high flux nanofiltration membrane for nanofiltration concentration of lithium carbonate solution, characterized in that: The high-flux nanofiltration membrane for nanofiltration concentration of lithium carbonate solution is prepared by the preparation method of the high-flux nanofiltration membrane for nanofiltration concentration of lithium carbonate solution as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of solvent-resistant composite nanofiltration membrane

    CN114247299A

  • PEI cast film with high energy storage density and high smoothness and preparation method thereof

    CN116262855A